Urgensi Pemahaman dan Kesadaran Produk Halal Pelaku Usaha di Kota Metro - Zulaikha, Siti; Lestari, Enny Puji; Imtihanah, Ani Nurul; Baidhowi, Mujib (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2024)
Metro City has a number of Micro, Small and Medium Enterprises (MSMEs) consisting of Muslims and non-Muslims. Muslim consumers are required in their religion to use only halal products, both processed and processed. Therefore, when searching or buying products, Muslim consumers pay attention to halal logos certified by religious authorities in Indonesia. With the need for halal products, business actors who are sensitive to halal business are also needed so as to affect consumer buying interest. With this, it is felt necessary to dedicate myself to my business to educate the understanding and awareness of business actors in Metro City. The author uses descriptive qualitative research methods in community service with data collection techniques with questionnaires and interviews with Muslim, non-Muslim MSME business actors and the PSMTI (Paguyuban Sosial Marga Tionghoa Indonesia) community in Metro City. The result of this community service is that MSME actors and the PSMTI community are aware and understand something that is prioritized in determining behavior towards what they eat, drink and use. Halal awareness of products is not only limited to understanding the products contained in choosing raw materials, production processes, production cleanliness and knowledge of the products that will be produced by MSME actors are very important. MSME business actors are very aware and understand 45%, aware and understand 48% and 7% are not aware and understand. The level of awareness and understanding of halal certificates for Muslim MSME actors is very dominant, although there are some who do not understand halal certificates because of ignorance from MSME business actors about the importance of halal certificates. Non-Muslim business actors and the PSMTI Community are also aware and understand the existing halal products